A novel ternary organic microwire radial heterojunction with high photoconductivity. Issue 20 (20th April 2016) - Zhang, Jianfeng; Xu, Xinjun; Yao, Chuang; Peng, Jinghong; Jia, Manping; Li, Lidong
Abstract : TCTA/PCBM/4CzIPN ternary radial heterojunction hybrid nanowires constructed from nanowires and nanoparticles by self-assembly exhibit high photoconductivity. Abstract : We fabricated a unique ternary organic hybrid microwire radial heterojunction by a facile method. First, 4, 4′, 4′′-tri( N -carbazolyl)triphenylamine (TCTA) microwires were prepared by solvent-evaporation-assisted self-assembly. Then, [6, 6]-phenyl-C61-butyric acid methyl ester (PCBM) nanoparticles were adsorbed onto the surface of the TCTA microwires, forming interesting corncob-like binary hybrid microwires. Finally, (4 s, 6 s )-2, 4, 5, 6-tetra(9 H -carbazol-9-yl)isophthalonitrile (4CzIPN) was adsorbed on the surface of the binary hybrid microwires to form ternary hybrid microwire radial heterojunctions. The thermally activated delayed fluorescence (TADF) material 4CzIPN was introduced into the donor–acceptor (D–A) system to form the ternary hybrid microwire radial heterojunction for the first time. The morphology has been confirmed by fluorescence microscopy, SEM and TEM. Interestingly, we found that this ternary hybrid microwire exhibited efficient photoconductivity by fabricating a bottom contact device; the photocurrent increased by more than 3 times compared with the reference device without 4CzIPN. By examining some reference devices, it can be inferred that the enhancement of the photoconductivity originates from the reversed intersystem crossing (RISC) process in 4CzIPN. This process can promote the formation of triplet excitons, thereby increasing the charge carrier concentration in the conductive channel of the microwire radial heterojunction. These high photoconductivity ternary microwires provide an efficient approach to improve the performance of photovoltaic devices and show promise for applications in organic integrated optoelectronics.